Olfactory Functioning and Depression: A Systematic Review - Taalman, Hannah; Wallace, Caroline; Milev, Roumen (Frontiers in Psychiatry, 2017)
Background. Research has demonstrated a reduction in olfactory functioning in patients with schizophrenia. This research has led to examination of olfactory functioning in other mental disorders, such as depression. There is a great deal of variation in the results generated from such research and it remains unclear as to how olfactory functioning is associated with or impacted by depression. Method. The current review examined the literature in accordance with PRISMA guidelines in order to generate a better understanding of this relationship and to identify if and what aspects of olfactory processing are altered. Through examination of the available literature from the databases PubMed, Ovid Medline, CINAL, and PsychINFO, fifteen manuscripts were selected to determine if there was a difference in olfactory processing - specifically central and peripheral processing – between depressed individuals and non-depressed controls. Results. The comparison of the fifteen studies showed that the majority of studies (9/15, 60%) found a difference in overall olfactory functioning between depressed individuals and non-depressed controls (p <0.05). Limitations. There is still a lack of definitive conclusions due to variation of which olfactory process was altered. Conclusions. Given the differences in the methodology and design of these studies, a possible solution that could eliminate the lack of clarity and reduce variation would be to adhere to a single, thorough methodology that examines and separates central and peripheral olfactory processing. Future research employing a uniform and validated methodology could provide more definitive conclusions as to how and if olfactory functioning is related depression.